Pengembangan Aplikasi Manajemen Logistic dan Purchasing pada Perusahaan Jasa Konstruksi berbasis Mobile (Studi Kasus: AMF-HAQ Engineering And Consultant) - Hendi Maryanto; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
AMF-HAQ is a construction and consulting company in Tangerang City which is engaged in civil engineering. In this company there is a logistics and purchasing division which is held by the warehouse manager. In the process of requesting goods, the project head of staff will make a request and submit it to the warehouse staff. The warehouse staff will submit the request to the warehouse manager, then the warehouse manager will approve the request. If the request for the goods is approved and there are some goods that are out of stock in the warehouse, the goods purchase process will be carried out. Until now, the entire process at the AMF-HAQ company is still done manually. All activities still use paper notes and Microsoft Excel. Meanwhile, the delivery of information regarding the tools for project fulfillment is still done verbally and there is no clear record. As a result of the manual process, problems arise such as frequent misinformation that causes inefficient use of construction equipment, slightly less effective employee performance, delays in project work, long project work and increased costs. This research will build an android-based logistics and purchasing management application with the waterfall method. From the test results, it was found that the unit test with the basis path got a value of 100%, then the validation test on 44 functional requirements obtained a value of 100% valid function. Meanwhile, for usability testing, it obtained a satisfactory score from the average respondent. And in the compatibility test on 3 android devices, namely on Android OS 5, 9, and 10.